Adolescent undernutrition in South Asia: a scoping review protocol. Issue 1 (23rd January 2020) - Estecha Querol, Sara; Al-Khudairy, Lena; Iqbal, Romaina; Johnson, Samantha; Gill, Paramjit
Abstract : Introduction: The aim of the protocol is to present the methodology of a scoping review that aims to synthesise up-to-date evidence on adolescent undernutrition in South Asia. Methods and analysis: The proposed scoping review will be guided by Arksey and O'Malley's framework and the Joanna Briggs Institute Reviewers' Manual. The scoping review question, eligibility criteria and search strategy will be based on the Population, Concept and Context strategy. We will conduct the search in electronic bibliographic databases (Medline (OVID), Embase, Cochrane Library, Web of Science, CINAHL, PsycInfo, Scopus) as well as various grey literature sources in order to synthesise and present the findings with descriptive statistics and a narrative description of both quantitative and qualitative evidence. Ethics and dissemination: This study protocol does not require ethical approval. This protocol will accurately describe the proposed scoping review that will map the evidence on adolescent undernutrition in South Asia. The proposed review aims to gather published and unpublished literature to inform policy and healthcare organisations as well as identify future research priorities in South Asia.